Evolution of Federalism in Modern India = Ewolucja federalizmu we współczesnych Indiach - Thankappannair, Ajayan (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
Federalism existed in ancient and medieval India in different forms. Immediately after the acquisition of power by the British, the colonial master began to centralize powers into the hands of the supreme government at Calcutta. The centralization of power reached its zenith with the enactment of the Charter Act of 1833. It formed one of the main reasons of the rebellion of 1857.
Keywords: India; Britain; federalism; government; constitution; Indie; Wielka Brytania; federalizm; rząd; konstytucja